First Late Triassic Record of a Paleoentomofauna from South America (Malargüe Basin, Mendoza Province, Argentina) - Brauckmann, Carsten (2010)
Late Middle Triassic to early Late Triassic insects from Argentina have been previously described from the Bermejo and Cuyana Basins where they have been recovered from the Ischichuca‐Los Rastros and Potrerillos‐Cacheuta Formations, respectively. The insect fauna discussed herein was collected during field studies in 1986/1987 from the Llantenes section (Norian to Rhaetian? Late Triassic), which is situated in the Malargüe Basin in southern Mendoza province. The insect remains were found in the upper part of the Llantenes section (Llantenes Formation), which is built up of two coarsening‐upwards cycles reflecting a deltaic progradation of a fluvial into a lacustrine environment (lower part), succeeded by repeated progradations into a floodplain‐dominated environment (upper part; with finds of insects, conchostracans, fish remains, plant fragments, and drifted logs). The new finds represent the youngest Triassic insect records described from Argentina and even from South America in its entirety. There is only one contemporaneous fossil assemblage in Gondwana: in the Clarence/Moreton Basin (Aberdare Conglomerate; Late Norian) in Australia. The new Triassic insects include an impression of an isolated Mecopterida‐like wing (Mendozachorista volkheimeri gen. et sp. nov.; Mendozachoristidae fam. nov.), coleopteran elytra of the Permosynidae (Ademosyne rosenfeldi sp. nov. and Ademosyne llantenesensis sp. nov.) and other isolated body fragments. This new Late Triassic entomofauna from Argentina is of considerable importance in the reconstruction of the biotic recovery of continental environments in Gondwana after the catastrophic mass extinction at the P/T boundary.